Pengetahuan, Sikap, dan Tindakan Petani Upsus dalam Mengendalikan Hama dan Penyakit Tanaman Padi - Kurniawan Effendi; Abdul Munif; I Wayan Winasa (Jurnal Ilmu Pertanian Indonesia, 2020)
The Special Efforts Program (Upsus) is an Indonesian government program to increase production/productivity of lowland rice to support the realization of food self-sufficiency. The Upsus targets are to increase the planting index by 0.5 and productivity by 0.3 tons/ha/GKP. The increase in planting index is achieved by the expansion of added planting, but the increase in productivity has not been reached optimally due to pest and disease attacks. The objective of this research was to determine the knowledge, attitudes, and actions of Upsus farmers in controlling pests and diseases, rice cultivation techniques, and implementation of Upsus in Karawang District. The research was conducted by distributing questionnaires to 60 farmers in Tempuran and Tirtajaya Sub-District at Karawang District. The respondents were selected by purposive sampling with the consideration of respondent being an active farmer, having at least 5 years of farming experience, and has ben a member of Upsus for at least 1 year. Most respondents have age in the range of 41-60 years, the highest education of elementary school, and have farming experience for 5-10 years. Pests and diseases are the biggest problems faced by the farmers. Upsus farmers used Ciherang and Inpari 32 varieties and the applications of pesticides were conducted according to the schedule. Most of the farmers could not distinguish between pests and diseases. The dominant pest and disease control carried out was the use of chemical pesticides. Keywords: diseases, pesticides, pests, Upsus